2019
DOI: 10.5194/isprs-archives-xlii-3-w9-63-2019
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Sensitivity Study of Aerosol Layer Height From Synthetic Multiangle Polarimetric Remote Sensing Measurements

Abstract: Abstract. Many previous studies have shown that multiangle, multispectral polarimetric remote sensing can provide valuable information on aerosol microphysical and optical properties, in which the aerosol layer height (ALH) is an important parameter but with less studies, especially in the near-ultraviolet (near-UV) and visible (VIS) wavelength bands. Based on the optimal estimation (OE) theory and information content analysis method, we focus on the sensitivity study of ALH with the synthetic data in the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In Section 4.2, we analyze the ability of MAPMU to detect the aerosol layer height for typical cases and show the impact of uncertainty for aerosol models. However, previous studies have shown that the aerosol vertical distribution is also affected by the aerosol model parameters (AOD, H), while the impact of these parameters generally appears to be similar in different aerosol types [7,29]. Therefore, in this section, we test the changes in ALH information under different aerosol optical depth conditions (AOD is from 0.2 to 1.0) and scale height conditions including near-ground aerosols and transported aerosols above the boundary layer (H is from 1 km to 5 km) for the vegetation surface.…”
Section: The Influence Of Adding Polarization Measurementsmentioning
confidence: 95%
See 4 more Smart Citations
“…In Section 4.2, we analyze the ability of MAPMU to detect the aerosol layer height for typical cases and show the impact of uncertainty for aerosol models. However, previous studies have shown that the aerosol vertical distribution is also affected by the aerosol model parameters (AOD, H), while the impact of these parameters generally appears to be similar in different aerosol types [7,29]. Therefore, in this section, we test the changes in ALH information under different aerosol optical depth conditions (AOD is from 0.2 to 1.0) and scale height conditions including near-ground aerosols and transported aerosols above the boundary layer (H is from 1 km to 5 km) for the vegetation surface.…”
Section: The Influence Of Adding Polarization Measurementsmentioning
confidence: 95%
“…Using Equation ( 15), we used the specified constant measurement errors from the previous section to calculate the DFS results resulting from various model errors. Previous research has shown that the DFS of the aerosol layer height will be affected by the aerosol types and has shown the differences, but the impact of AOD generally appear similar in different aerosol types [7,29]. Therefore, we concentrated on AOD = 0.6 and scale height = 2 km as a demonstration.…”
Section: The Influence Of Model Errorsmentioning
confidence: 99%
See 3 more Smart Citations